Social relationships and cognitive decline: a systematic review and meta-analysis of longitudinal cohort studies - Kuiper, Jisca S.; Zuidersma, Marij; Zuidema, Sytse U.; Burgerhof, Johannes G. M.; Stolk, Ronald P; Oude Voshaar, Richard C.; Smidt, Nynke (International journal of epidemiology, 2016)
Although poor social relationships are assumed to contribute to cognitive decline, meta-analytic approaches have not been applied. Individual study results are mixed and difficult to interpret due to heterogeneity in measures of social relationships. We conducted a systematic review and meta-analysis to investigate the relation between poor social relationships and cognitive decline. MEDLINE, Embase and PsycINFO were searched for longitudinal cohort studies examining various aspects of social relationships and cognitive decline in the general population. Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled using random effects meta-analysis. Sources of heterogeneity were explored and likelihood of publication bias was assessed. We stratified analyses according to three aspects of social relationships: structural, functional and a combination of these. We identified 43 articles. Poor social relationships predicted cognitive decline; for structural (19 studies): pooled OR: 1.08 (95% CI: 1.05-1.11); functional (8 studies): pooled OR: 1.15 (95% CI: 1.00-1.32); and combined measures (7 studies): pooled OR: 1.12 (95% CI: 1.01-1.24). Meta-regression and subgroup analyses showed that the heterogeneity could be explained by the type of social relationship measurement and methodological quality of included studies. Despite heterogeneity in study design and measures, our meta-analyses show that multiple aspects of social relationships are associated with cognitive decline. As evidence for publication bias was found, the association might be overestimated and should therefore be interpreted with caution. Future studies are needed to better define the mechanisms underlying these associations. Potential causality of this prognostic association should be examined in future randomized controlled studies.